Transient characteristics of nitrogen gas-pulsed electron cyclotron resonance plasma - Park, YJ; Ozasa, K; OKeeffe, P; Aoyagi, Y; Min, SK (AMER INST PHYSICS, 1996)
Transient optical emission characteristics of a nitrogen gas-pulsed electron cyclotron resonance (ECR) plasma have been investigated as a first step towards understanding the nature of a nitrogen gas-pulsed plasma. We observed different transient optical emission profiles for the first negative N-2(+), the second positive N-2*, and the first positive N-2* emission bands in nitrogen gas-pulsed ECR plasma that are closely related to the pressure changes in a discharge cavity of the plasma source. On the basis of the transient emission profiles, optical emission spectra over the wavelength range 300-700 nm were obtained for three specific time regions within the pulse. During the gas-pulsed injection period large ratios of N-2*/N-2(+) (2.5-7.1) and low electron temperatures (1.2 eV) were observed. On the other hand, small ratios of N-2*/N-2(+) (0.3) and high electron temperature (2.5 eV) were recorded 0.65 a after stopping the gas-pulsed injection. These observed N-2*/N-2(+) ratios are interpreted in terms of different excitation processes and electron temperatures (T-e) due to the surge of neutral N-2 gas. The N-2*/N-2(+) ratios in an ECR gas-pulsed plasma are 5-7 times higher than those in continuous wave plasma. Through timing optimization of the transient characteristics, nitrogen gas-pulsed ECR plasma is considered to be a useful candidate for high efficiency p -type high doping in Zn(Se,Te) semiconductors or for the plasma deposition of nitride films. (C) 1996 American Vacuum Society.
Keywords: MOLECULAR-BEAM EPITAXY; HYDROGEN PLASMA; P-TYPE; GROWTH; ZNSE